Sensitivity Analysis of Coal Rib Stability for Internal Mine Dump in Opencast Mine by Finite Element Modelling - Gupta T.; Rai R.; Jaiswal A.; Shrivastva B.K. (My University, 2025)
The present paper discusses the impact of the geometrical parameters of the coal rib and the mine dump on the stability of the coal rib. The geometrical parameters such as the slope angle, the height of dragline dump, the height of main dump, the gradient of seam and the thickness of coal rib have been considered as input to the numerical model for the stability analysis of the coal rib. Sensitivity analysis has been performed based on the results of the analysis in term of factor of safety of the coal rib. The input parameters have been classified in terms of significance (i.e. very high significance, high significance medium significance and low significance). The factor of safety is more influenced by highly significant parameters. The height and the slope angle of dragline dump and the thickness of the coal rib are highly significant parameters for the stability of the coal rib. The gradient of the seam is a medium significant parameter whereas, height of main dump and the number of dragline cut dump are low significant parameters for stability of coal rib. © 2014 Springer International Publishing Switzerland.